2016
DOI: 10.3109/13816810.2015.1130154
|View full text |Cite
|
Sign up to set email alerts
|

SPATA7: Evolving phenotype from cone-rod dystrophy to retinitis pigmentosa

Abstract: Background SPATA7 mutations have been associated with different autosomal recessive retinal degeneration phenotypes. Long-term follow-up has not been described in detail. Materials and methods A Hispanic patient with SPATA7 mutations was evaluated serially over a 12-year period with kinetic and static chromatic perimetry, optical coherence tomography (OCT) and fundus autofluorescence (AF) imaging. Electroretinography (ERG) was performed at the initial visit. Results The patient was homozygous for a mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…While the overall topography of the retinal dysfunction awaits confirmation in larger groups of patients with RDH12-IRDs, the pattern observed in this work, taken together with those of previous reports, strongly suggests that autosomal recessive mutations in RDH12 cause a predominantly severe central retinal degeneration that is consistent with an early CRD phenotype. 32,35,[54][55][56][57] Reports of CRD phenotypes in milder forms of RDH12-IRD supports a common disease expression with a wide spectrum of severity in RDH12-IRD. 32,44,55 The disease mechanisms in RDH12-IRD are not fully understood, but the severity and early presentation of the phenotype that results suggest a critical role in human retinal physiology.…”
Section: Discussionmentioning
confidence: 82%
“…While the overall topography of the retinal dysfunction awaits confirmation in larger groups of patients with RDH12-IRDs, the pattern observed in this work, taken together with those of previous reports, strongly suggests that autosomal recessive mutations in RDH12 cause a predominantly severe central retinal degeneration that is consistent with an early CRD phenotype. 32,35,[54][55][56][57] Reports of CRD phenotypes in milder forms of RDH12-IRD supports a common disease expression with a wide spectrum of severity in RDH12-IRD. 32,44,55 The disease mechanisms in RDH12-IRD are not fully understood, but the severity and early presentation of the phenotype that results suggest a critical role in human retinal physiology.…”
Section: Discussionmentioning
confidence: 82%
“…In retrospect this finding is maybe not surprising. Peripheral to TZ, retinal function is substantially reduced, ONL thickness is relatively retained while OS are very abnormal in many IRDs 12 , 87 , 93 , 103 , 104 . Structural abnormalities of the rod OS beyond that expected from loss of neighboring rod cells and functional abnormalities of the rod system beyond that expected from reduced OS volume could combine to contribute to the RFD.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we identified disease-causing mutations in SPATA7 , encoding spermatogenesis associated protein 7 (MIM 609868), in families with LCA and juvenile RP (Wang et al, 2009). Following this report, additional studies have identified SPATA7 mutations in patients with these diseases, clearly demonstrating a causal link between SPATA7 and human retinal disease (Kannabiran et al, 2012; Mackay et al, 2011; Matsui et al, 2016; Mayer et al, 2015; Perrault et al, 2010; Watson et al, 2014). Recently, we examined the effects of germline disruption of Spata7 and showed that Spata7 knockout (KO) mice exhibit early onset retinal degeneration, and the phenotype can be rescued by gene therapy (Eblimit et al, 2015; Zhong et al, 2015).…”
Section: Introductionmentioning
confidence: 62%